THE MARRIAGE PRACTICES OF INDIGENOUS PEOPLES OF LAMPUNG SEBATIN FROM THE PERSPECTIVE OF ISLAMIC FAMILY LAW IN INDONESIA - Idham, I.; Faizal, Liky; Qohar, Abdul; Hanif, H. (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study analyzes the problems related to the existence of Lampung Sebatin Indigenous Marriages. Where the Lampung indigenous people Sebatin started a new life order in marriage combining custom and Islamic law. Marriage is divided into two ways, namely Nyakak/ Jujokh and Semanda marriages. The traditional marriage procedures have values and norms or rules. The problem in this research is how the practice of marriage and how the description of the relationship between customary law and Islamic law as well as positive law in Indonesia in the marriage of the indigenous community of Lampung Sebatin. The purpose of this study was to obtain information about: first, the practice of marriage traditional Lampung Sebatin procedures; and Second, positive law and Islamic law in the traditional marriage customs of Lampung Sebatin. This study uses the qualitative research method with a sociological legal approach that focuses on the process of implementing marriage based on Islamic law and customary law with predetermined objectives. The research data were obtained using the interview method conducted on the object of research or respondents. The findings of this study indicate that first, the practice of marriage traditional Lampung Sebatin in its implementation uses Islamic law, but there are several processions such as pre-marriage and after-marriage. Marriage Lampung traditional customs are Sebatin divided into two, namely Nyakak/ Jujokh and Semanda with the traditional stages before, the implementation customary stages and the customary stages after marriage and the pattern of settling after marriage. Second, the law of marriage in the teachings of the Islamic religion with the law on marriage, in the procedure of marriage, in Nyakak/ Jujokh and Semanda is general it can be said that line, in practice it is in accordance with the basis and reference, namely the law on marriage is al-Quran, al-Sunnah, Qaidah Fighiyah and Consensus (Ijma) of Muslims in Indonesia.Keywords: Marriage, Tradition, Lampung, Sebatin, Islamic Law